2023
DOI: 10.1111/iji.12614
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in low‐to‐medium‐affinity Fcγ receptors and autoimmune neutropenia in early childhood in a Danish cohort

Abstract: Autoimmune neutropenia (AIN) in early childhood is caused by autoantibodies directed against antigens on the neutrophil membrane and is a frequent cause of neutropenia in children. Association of AIN with Fcγ receptor (FCGR) 3B variants is well described. In this study, we investigate genetic variations in the FCGR locus and copy number variation of FCGR3B. A total of 130 antibody‐positive AIN patients, 64 with specific anti‐HNA‐1a antibodies and 66 with broad‐reacting anti‐FcγRIIIb antibodies, were genotyped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 63 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…This differentiation between HLA associations and HNA‐1a antibody specificities in AIN patients has been observed previously for both DRB1 and DQB 1 5 but also in regards to genetic variation in low‐to‐medium Fcγ receptors 6 . In this study, we observed differences regarding HLA class I and II alleles.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This differentiation between HLA associations and HNA‐1a antibody specificities in AIN patients has been observed previously for both DRB1 and DQB 1 5 but also in regards to genetic variation in low‐to‐medium Fcγ receptors 6 . In this study, we observed differences regarding HLA class I and II alleles.…”
Section: Discussionsupporting
confidence: 86%
“…33 This differentiation between HLA associations and HNA-1a antibody specificities in AIN patients has been observed previously for both DRB1 and DQB1 5 but also in regards to genetic variation in low-to-medium Fcγ receptors. 6 In this study, we observed differences regarding HLA class I and II alleles. DRB1*01, which is unique to anti-HNA-1a positivity, has been reported to be protective for sarcoidosis [34][35][36][37] and a predisposing factor in diseases such as recurrent lymphocytic meningitis and juvenile idiopathic arthritis in Hungarian patients, 38,39 exhibiting contrary effects depending on the disease.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Study II contains two papers. The first paper is "Genetic variations in low-to-mediumaffinity Fcγ receptors and autoimmune neutropenia in early childhood in a Danish cohort" [181]. In this paper, copy numbers and genetic variation in the FCGR2/3 locus were investigated in 130 AIN patients and compared to healthy control groups of different sizes.…”
Section: Study IImentioning
confidence: 99%